Reduced order finite element modelling of a nonlinear system: an application to induction heating system. (2015) - Guha, Paramita; Nabi, Mashuq-un
In this paper, a fully dynamic three dimensional induction heating system having axial symmetry is considered. The model is described by nonlinear partial differential equations and nonlinearities are due to dependence of specific heat, thermal and electrical conductivities on temperatures. A mathematical model in nonlinear ordinary differential form is obtained. A reduction technique is applied to obtain a reduced model for further use. Error due to the reduction is obtained and it has been observed that the error is quite small thus illustrating the validity of this model. Numerical results and possible extensions are given.